Neural mechanisms of goal-contingent task disengagement: Response-irrelevant stimuli activate the default mode network. (August 2016) - Anderson, Brian A.; Folk, Charles L.; Courtney, Susan M.
Abstract: As we experience the world, we must decide not only when and how to act based on input from the environment, but also when to avoid responding in situations where acting could lead to a detrimental outcome. The ability to regulate behavior in this way requires flexible cognitive control, as the same stimulus may call for a response in one context but not in another. In this sense, explicit non-responding can be characterized as an active, goal-directed cognitive process. Little is known about the mechanisms by which a currently active goal state modulates information processing to support the avoidance of undesired responding. In the present study, participants executed or withheld responses to a color target based whether its color matched that of a cue at the beginning of each trial. Behavioral and neural responses to task-irrelevant stimuli appearing as distractors were examined as a function of their relationship to the currently response-relevant color indicated by the cue. We observed a robust pattern in which stimuli possessing the currently response-irrelevant feature activate the default mode network (DMN), which was associated with a behavioral cost on trials in which this stimulus competed with a response-relevant target. Our findings reveal a role for the DMN in goal-directed cognitive control, facilitating active disengagement based on contextually-specific task demands.